Muscle activity characteristics of a swimmer`s front and rear leg during a kickstart - Objected for elite swimmer case study - Sato, D.; Suito, H.; Mizukami, T.; Kusanagi, K.; Takahashi, S. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
Numerous studies have reported on the kinematics and kinetics during a swimmer`s kickstart. However, no studies measuring the muscle activity of the lower limbs during the kickstart have been presented. This study investigated the muscle activity of both the front lower limb and the rear lower limb during a swimmer`s kickstart and identified its characteristics. The participant was a national-level competitive male swimmer - 24 years old, 200-m breaststroke Fédération Internationale de Natation (FINA) points: 888 - who performed the breaststroke at the starting block for 15-m maximum effort at two kickstart conditions: right lower limb is front (LF) and right lower limb is rear (LR). Trials were recorded using a video camera (120 frame/s) from the sagittal movement, and surface electromyographic (EMG) data were recorded from eight right lower limb muscles: rectus femoris (RF), vastus lateralis (VL), biceps femoris (BF), tibialis anterior (TA), medial head of gastrocnemius (MHG), lateral head of gastrocnemius (LHG), soleus (SO), and gluteus maximus (GM).The EMG data were filtered using a Butterworth bandpass filter (10 - 500 Hz), and the root mean square (RMS) was calculated on a 50-ms window of data. The result showed that the muscle activity in lower limbs during the kickstart was in the sequence RF, VL, GM, TA, MHG, and LHG, working in accordance with the movement of each joint.